2014
DOI: 10.4314/sajas.v44i2.4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of <i>in ovo</i> administration of amino acids on hatchability and performance of meat chickens

Abstract: The effects of in ovo amino acid administration on hatchability traits and post-hatch performance were studied using eggs from a meat-type breeder flock (Ross) at 38 weeks of age. On day 15 of incubation, five treatments were applied, consisting of six replicates with 16 eggs per replicate. The treatments consisted of a non-injected negative control; a positive control in which saline was injected; and three treatments with saline, containing 23.72 mg lysine, glutamine, glycine and proline (AA1); 23.60 mg argi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
24
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 23 publications
4
24
1
5
Order By: Relevance
“…Previous studies that used different BCAA mixtures (Bhanja & Mandal, 2005;Kita et al, 2015;Kop-Bozbay & Ocak, 2015b) indicated that there were no differences in hatchability and chick weights. Likewise, in several studies, IOF has increased hatchability (Uni et al, 2005;Shafey et al, 2013Shafey et al, , 2014 (2009), it may be expected that an excess of 8 g in the PW of the BCAAb group will result in an excess of about 80 g at slaughter.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Previous studies that used different BCAA mixtures (Bhanja & Mandal, 2005;Kita et al, 2015;Kop-Bozbay & Ocak, 2015b) indicated that there were no differences in hatchability and chick weights. Likewise, in several studies, IOF has increased hatchability (Uni et al, 2005;Shafey et al, 2013Shafey et al, , 2014 (2009), it may be expected that an excess of 8 g in the PW of the BCAAb group will result in an excess of about 80 g at slaughter.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies that used different BCAA mixtures (Bhanja & Mandal, ; Kita et al, ; Kop‐Bozbay & Ocak, ) indicated that there were no differences in hatchability and chick weights. Likewise, in several studies, IOF has increased hatchability (Uni et al, ; Shafey et al, , ) and improved the viability and weight of chicks and the development of intestine and muscle (Uni et al, ; Shafey, Alodan, Al‐Ruqaie, & Abouheif, ), depending on the nutrient injected. In contrast to the report by Shafey et al (), the IOF of BCAAb reduced the relative EmW, whereas it increased the yolk‐free and the relative PWs.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…in ovo iron administration at 80 μg/egg improved humoral immune status and post‐hatch growth, whereas copper at 8 μg/egg enhanced the cellular immune response (Goel, Bhanja, Mehra, Pande, & Majumdar, ) in broiler chicken. in ovo glucose administration, modulated humoral immunity and fructose/ribose administration improved cellular immunity (Shafey, Mahmoud, Alsobayel, & Abouheif, ). Bhanja et al.…”
Section: Discussionmentioning
confidence: 99%